Sport and Exercise Psychology Studies in Brazil: Performance or Health? - Fiorese, Lenamar; Rodacki, André Luiz Felix; Caruzzo, Nayara Malheiros; Moreira, Caio Rosas; Contreira, Andressa Ribeiro; de Lima, Aline Mendes; Fortes, Leonardo de Sousa; Vissoci, João Ricardo Nickenig; Stefanello, Joice Mara Facco (Frontiers in Psychology, 2019)
The low professional insertion of psychologists in Brazilian sports teams, as well as the Sport Psychology course being seldom offered in undergraduate Psychology courses, may reflect in the current scenario of scientific research in Brazil. It is still not clear what Graduate Programs (GPs) have adopted directions regarding the development of studies in Sport and Exercise Psychology (SEP) research fields since an assessment or mapping of scientific knowledge production in this area has not yet been performed involving Exercise and Sport Science and Psychology GPs. This study aimed at investigating institutional research and their themes in SEP from these graduate programs. Studies were selected and retrieved from a national database (Sucupira Platform), that contains all registered researches from all Exercise and Sport Science (n=31) and Psychology (n=84) GPs in the country. Data were analyzed through R software using text mining techniques, latent semantic analysis, and K-means clustering. Results revealed that research involving SEP is predominantly being developed at Exercise and Sport Science GPs (n=171; p<0.01) in comparison to psychology GPs (n=39), mostly located in the south and southeast regions of Brazil. This research has focused on the effects of physical exercise and quality of life, while Psychology GPs have analyzed sport as associated with health and education, as a way to promote social support and to study sports' psychological aspects. It was concluded that Exercise and Sport Science GPs had the most significant contribution to SEP. Investigations were focused on the interface of exercise with quality of life, health, and education, with gaps existing in programs advancing in the studies on sports and performance.